Processing method of moisture-absorbing and quick-drying ready-made easy-care shirt
By evenly spraying the non-iron finishing agent on the shirt and performing multi-step process processing, nano-adsorbent powder and fibrous connecting materials are used to solve the problem of cotton shirts being deformed after multiple washes and sweating at high temperatures, achieving the effect of moisture absorption and rapid drying and non-ironing, and improving the overall performance of the shirt.
Patent Information
- Application Number
- CN202510085250.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
AI Technical Summary
Existing cotton shirts will deform after multiple washes, affecting the appearance effect, and are easily impregnated by sweat or oil in high temperatures or sweating, affecting comfort and aesthetics.
A processing method is adopted, which includes uniformly atomizing and spraying the non-iron finishing agent on the outer and inner surfaces of the shirt, pre-baking, pressing, baking, freezing and washing and drying, and using nano-adsorbent powder and fibrous connecting materials to improve the moisture absorption and fast drying performance of the shirt and the non-iron effect.
The shirt is absorbed and quickly dry and iron-free, which improves the practicality, comfort and aesthetics of the shirt, while enhancing the flatness and tear strength of the fabric.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite fabric processing, and in particular relates to a method for processing a moisture-absorbing quick-drying ready-made ironing-free shirt. Background Art
[0002] Composite fabric is a new type of material made by bonding one or more layers of textile materials, non-woven materials and other functional materials. Fabric is the material used to make clothing. Fabric includes woven fabric and knitted fabric. Common clothing fabrics include: cotton, linen, silk, woolen, leather, chemical fiber, blended, modal, etc. Textile is roughly divided into two processes: spinning and weaving. Fabric finishing agent is a liquid coated on the fabric, which can change the surface properties of the fabric, thereby giving the fabric special functions. There are many varieties, such as: water-repellent and oil-repellent finishing agent, anti-fouling finishing agent and easy-to-remove finishing agent, antibacterial, anti-mildew and anti-mite finishing agent, non-ironing finishing agent, etc. Ironing is an important process in the garment sewing process. It has three main functions: (1) to shrink the fabric by spraying and ironing to remove wrinkles; (2) to make the garment smooth and straight through heat setting treatment; (3) to use the shrinkage of the fiber to appropriately change the fiber tension and shrinkage and the density and direction of the warp and weft structure of the fabric to shape the three-dimensional shape of the garment, so as to achieve the purpose of beautiful three-dimensional shape and comfortable wearing.
[0003] Compared with chemical fiber fabrics, cotton shirts have excellent moisture absorption and moisture retention. However, cotton fibers have the disadvantages of poor wrinkle resistance, easy deformation, and large shrinkage. Cotton shirts will show different degrees of deformation after multiple washings, affecting the appearance of the shirts. For this reason, the shirts need to be treated with a non-ironing finishing agent.
[0004] At present, shirts are usually worn close to the skin, and are usually worn in formal, public, and important occasions. When worn by people with sweaty or oily skin or in high temperatures, the shirts may be soaked with sweat or oil, which seriously affects comfort and appearance.
[0005] Therefore, how to process shirts so that they can be both iron-free and quick-drying, thereby improving the practicality, comfort and aesthetics of the shirts, is a technical problem that technicians in this field urgently need to solve. Summary of the invention
[0006] The invention aims to provide a method for processing a moisture-absorbing quick-drying ready-made ironing-free shirt.
[0007] In order to achieve the above object, the technical solution of the present invention is as follows:
[0008] A method for processing a moisture-absorbing quick-drying ready-made ironing shirt comprises the following steps performed in sequence:
[0009] 1) uniformly spraying a non-ironing finishing agent on the outer surface and the inner surface of the shirt, wherein the non-ironing finishing agent contains a nano adsorbent powder, and the nano adsorbent powder includes at least one of silica gel, activated alumina and molecular sieve;
[0010] 2) Pre-baking: pre-baking the shirt obtained in step 1);
[0011] 3) Pressing: Pressing each part of the shirt obtained in step 2) respectively;
[0012] 4) Baking: Baking the pressed shirt obtained in step 3);
[0013] 5) Freezing: The baked shirt obtained in step 4) is placed in a freezer for freezing;
[0014] 6) washing and drying to obtain a moisture-absorbing, quick-drying, iron-free shirt;
[0015] Wherein, the temperature of the freezing chamber in step 5) is 0-10°C, and the freezing treatment time is 0.1h-10h.
[0016] Preferably, the non-ironing finishing agent comprises: 60-200 g / L of non-ironing resin, 10-50 g / L of fiber protective agent, 20-60 g / L of softener, and 15-25 g / L of catalyst;
[0017] The pH value of the permanent ironing finishing agent is 3.5-6.
[0018] Preferably, the content of the nano-adsorbent powder in the permanent-ironing finishing agent is 30-70 g / L, and the particle size of the nano-adsorbent powder is 10 nm-10000 nm.
[0019] Preferably, the non-ironing finishing agent further comprises a fibrous connecting material, wherein the fibrous connecting material comprises at least one of nanofibers, cellulose and whiskers;
[0020] The content of the fibrous connecting material in the non-ironing finishing agent is 20-60 g / L, and the particle size of the fibrous connecting material is 10 nm-10000 nm.
[0021] Preferably, a manual pre-ironing process is provided between step 2) and step 3), in which the parts of the shirt obtained in step 2) are manually ironed to have creases, and step 3) is performed by pressing along the creases.
[0022] Preferably, in step 1), the shirt has a liquid content of 50% to 90% after applying the non-ironing finishing agent;
[0023] After the pre-drying in step 2), the shirt is dehydrated by 50% to 90%.
[0024] Preferably, the baking temperature in step 4) is 100° C. to 150° C., and the baking time is 5 min to 25 min.
[0025] This application has achieved the following beneficial technical effects:
[0026] The present invention performs low-temperature freezing treatment on the shirt after the baking process and ensures a high humidity in the freezing chamber, giving the shirt after high-temperature baking a certain humidity, so that the moisture regain rate is further improved;
[0027] Compared with the shirt fabric cooled at room temperature, the flatness is significantly improved, the tearing strength and breaking strength of the fabric are also improved to a certain extent, and the fabric feels smoother;
[0028] The high-temperature baking treatment causes the resin monomers in the wrinkle-free finishing agent to undergo permanent cross-linking reaction with the hydrogen bonds on the fibers. The cross-linking reaction will produce small molecular impurities and odorous gases. Sufficient freezing time can also allow the odor of the shirt to fully dissipate, thereby improving the environmental friendliness of the wrinkle-free shirt and achieving wrinkle-free treatment of the shirt.
[0029] In the present application, the non-ironing finishing agent contains nano-adsorbent powder, and the nano-adsorbent powder includes at least one of silica gel, activated alumina and molecular sieve:
[0030] First, since the non-ironing finishing agent is an organic liquid and contains resin, the non-ironing finishing agent has a certain adhesive function, so that the particles of the nano-adsorbent powder can be glued and fixed on the inner surface of the shirt and the outer surface of the fibers in the yarn on the outer surface by the non-ironing finishing agent, and the adhesive force is relatively large, the adhesiveness is relatively firm, and it is not easy to fall off;
[0031] Second, the outer diameters of the yarn and the fibers in the shirt are both about 0.01mm-2mm, which are visible to the naked eye. Therefore, nano-sized adsorbent particles are selected, which are invisible to the naked eye. The outer diameters of the yarn and the fibers in the shirt are 10-10,000 times the outer diameters of the nanoparticles. Therefore, compared with the yarn and the fibers in the shirt, the nanoparticles are very small. The nanoparticles can be densely bonded and fixed on the outer surface of the yarn and the fibers in the shirt. Such tiny nanoparticles cannot be felt by the skin and will not wear the skin.
[0032] Third, because silica gel, activated alumina and molecular sieve are all porous materials, they all have huge surface areas, strong adsorption and drying properties, and strong water absorption, oil absorption and odor absorption properties. The sweat, oil and odor gases produced by the skin can be quickly absorbed by silica gel, activated alumina and molecular sieves and then stored in the pores of the porous structure of silica gel, activated alumina and molecular sieves. At this time, silica gel, activated alumina and molecular sieves are like a storage pool. The strong adsorption and storage capacity of the storage pool can first absorb and store the sweat, oil and odor gases produced by the skin, so that the sweat, oil and odor gases are separated from the skin and the fibers in the shirt, so that the skin and the shirt are always clean and fresh, thereby achieving the purpose of moisture absorption and quick drying of the shirt, and improving the practicality, comfort and aesthetics of the shirt;
[0033] Fourth, the sweat, oil and odor gas adsorbed and stored in silica gel, activated alumina and molecular sieve are slowly released into the atmosphere until they are completely discharged or released and dissolved in water when washing the shirt, and finally the silica gel, activated alumina and molecular sieve are regenerated. After regeneration, they continue to adsorb and store the sweat, oil and odor gas secreted by the skin later, that is, silica gel, activated alumina and molecular sieve can adsorb and regenerate;
[0034] Fifth, the added silica gel, activated alumina and molecular sieve act as an intermediate transition carrier, first quickly adsorbing and storing them inside themselves and then slowly releasing them into the atmosphere, or dissolving them in water when the shirt is washed with water for removal. This absorbs and dries faster, more thoroughly and cleaner than the traditional method of first transferring sweat, oil and odor gases on the skin to the shirt and then releasing them into the atmosphere.
[0035] In the present application, although the particles of the nano-adsorbent powder can be firmly fixed on the inner surface and the outer surface of the fibers in the yarn on the outer surface of the shirt by the non-ironing finishing agent, the adhesive connection and the adhesive force are both large, but in order to further improve the adhesion and connection strength between the particles of the nano-adsorbent powder and the yarn and the fibers in the shirt, the non-ironing finishing agent in the present application also includes a fibrous connecting material, and the fibrous connecting material includes at least one of nanofibers, cellulose and whiskers;
[0036] The yarns and fibers in the shirt are all fibrous materials, while the nano-adsorbent powder is usually a granular material. The two materials are different in appearance and other aspects. The differences and interface effects between the two will limit the adhesion and connection strength between the particles of the nano-adsorbent powder and the yarns and fibers in the shirt. The above-mentioned fibrous connecting material is the same fibrous material as the yarns and fibers in the shirt. Both are fibrous materials, so that there are no negative effects such as interface effects that exist when different materials are connected between the fibrous connecting material and the yarns and fibers in the shirt. The two, which are both fibrous materials, can be naturally and spontaneously glued together or even formed into one, with greater connection strength and adhesion. Therefore, the role of the fibrous connecting material here is similar to the reinforcing ribs in mechanical processing, which can strengthen the connection strength and adhesion of the entire system, thereby improving the adhesion and connection strength between the particles of the nano-adsorbent powder and the yarns and fibers in the shirt. The particles of the nano-adsorbent powder are glued more firmly and are less likely to fall off, thereby making the service life of the moisture absorption and quick-drying function of the shirt longer and more durable. DETAILED DESCRIPTION
[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. The described embodiments are only part of the embodiments of the present invention, not all of them. Therefore, based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] The present application provides a method for processing a moisture-absorbing, quick-drying, non-ironing ready-made shirt, comprising the following steps performed in sequence:
[0039] 1) uniformly spraying a non-ironing finishing agent on the outer surface and the inner surface of the shirt, wherein the non-ironing finishing agent contains a nano adsorbent powder, and the nano adsorbent powder includes at least one of silica gel, activated alumina and molecular sieve;
[0040] 2) Pre-baking: pre-baking the shirt obtained in step 1);
[0041] 3) Pressing: Pressing each part of the shirt obtained in step 2) respectively;
[0042] 4) Baking: Baking the pressed shirt obtained in step 3);
[0043] 5) Freezing: The baked shirt obtained in step 4) is placed in a freezer for freezing;
[0044] 6) washing and drying to obtain a moisture-absorbing, quick-drying, iron-free shirt;
[0045] Wherein, the temperature of the freezing chamber in step 5) is 0°C to 10°C, and the freezing treatment time is 0.1h to 10h.
[0046] In one embodiment of the present application, the non-ironing finishing agent comprises: 60-200 g / L of non-ironing resin, 10-50 g / L of fiber protective agent, 20-60 g / L of softener, and 15-25 g / L of catalyst;
[0047] The pH value of the permanent ironing finishing agent is 3.5-6.
[0048] In one embodiment of the present application, the content of the nano-adsorbent powder in the permanent-ironing finishing agent is 30-70 g / L, and the particle size of the nano-adsorbent powder is 10 nm-10000 nm, preferably 10 nm-200 nm.
[0049] In one embodiment of the present application, the non-ironing finishing agent further comprises a fibrous connecting material, wherein the fibrous connecting material comprises at least one of nanofibers, cellulose and whiskers;
[0050] The content of the fibrous connecting material in the non-ironing finishing agent is 20-60 g / L, and the outer diameter of the fibrous connecting material is 10 nm-10000 nm, preferably 10 nm-200 nm.
[0051] In one embodiment of the present application, a manual pre-ironing process is provided between step 2) and step 3), in which each part of the shirt obtained in step 2) is provided with creases by manual ironing, and step 3) is performed by pressing along the creases.
[0052] In one embodiment of the present application, the liquid content of the shirt after applying the non-ironing finishing agent in step 1) is 50 wt % to 90 wt %;
[0053] After pre-drying in step 2), the shirt has been dehydrated by 50 wt% to 90 wt%.
[0054] In one embodiment of the present application, the baking temperature in step 4) is 100° C. to 150° C., and the baking time is 5 min to 25 min.
[0055] In the present application, a manual pre-ironing process is also provided, in which each part of the shirt obtained in step 2) is manually ironed to have folds, and step 3) is pressed along the folds. Manual pre-ironing can give the clothes a certain prototype and improve the efficiency of pressing. If the position of the folds of the shirt after pressing is deviated, it needs to be reworked and sprayed with a non-ironing finishing agent after treatment. The process arrangement of pre-ironing first and pressing later can significantly reduce the defective rate and rework rate.
[0056] In the present application, in order to optimize the hydrophilicity of the wrinkle-free shirt fabric, the wrinkle-free resin is at least one selected from modified dihydroxymethyl dihydroxyethylene urea, nano-dispersed self-crosslinked polyether polyurethane, and modified alkyl dihydroxyethylene urea. A formaldehyde-free nano-scale self-crosslinked polyether polyurethane dispersion is used. The molecules of the self-crosslinked polyether polyurethane are small and can penetrate into and between the fibers. The main chain of the polyurethane contains hydrophilic hydroxyl and carboxyl groups, and the ether bonds in the polyether are also hydrophilic, which can significantly improve the hydrophilicity of the shirt fabric after treatment. The film formed by the polyurethane resin has more air pores and better air permeability.
[0057] In the present application, in order to improve the wrinkle recovery angle of the fabric after the wrinkle-free treatment and optimize the tear strength and abrasion strength of the fabric, the fiber protective agent is at least one selected from the silicone emulsion of elastic polyurethane and the co-emulsion of oxidized polyethylene homopolymer and amino silicone oil.
[0058] In the present application, in order to improve the damage of the wrinkle-free finishing agent to the strength of the fabric and give the fibers in the shirt fabric a soft and fluffy feel, the softener is at least one selected from amino polysiloxane containing polyether groups and polyethylene polysilicon compound synthetic bodies.
[0059] In the present application, in order to accelerate the cross-linking reaction rate between the resin or cross-linking agent and the fiber, reduce the reaction temperature and shorten the reaction time, the catalyst is magnesium chloride or a composite catalyst; the composite catalyst is composed of a metal salt catalyst and a hydroxycarboxylic acid, the metal salt catalyst is at least one selected from magnesium chloride, magnesium nitrate, zinc chloride, and zinc nitrate, the hydroxycarboxylic acid is at least one of citric acid, dihydroxymethylpropionic acid, and 2,3-dihydroxysuccinic acid, and the mass percentage of the metal salt catalyst in the composite catalyst is 80% to 90%.
[0060] In the present application, the pH regulator is used to ensure that the non-ironing finishing agent is maintained at a suitable cross-linking pH. The pH regulator is selected from acetic acid, citric acid-sodium citrate buffer, acetic acid-sodium acetate buffer and sodium dihydrogen phosphate-citric acid buffer. The raw materials of citric acid and sodium citrate in the above buffer are basically derived from food, which will not harm human health, and is an excellent chelating agent / complexing agent in chemistry. Sodium citrate has a good affinity for Ca 2+ Mg 2+ Metal ions have good complexing ability and work synergistically with the catalyst to precipitate hydrogen ions from the finishing agent, promoting more thorough cross-linking of the resin.
[0061] In the present application, the hydrophilicity test shows that the greater the content of nano-dispersed self-cross-linked polyether polyurethane in the wrinkle-free resin, the better the hydrophilicity of the shirt fabric after wrinkle-free treatment. The covering film layer formed by polyurethane on the fiber surface reduces the friction and surface tension between the fibers, making the fibers easier to slide, thereby improving the overall feel of the fabric.
[0062] In the present application, the buffer is configured according to the pH value of the standard buffer. The pH value of the reaction can be controlled within a certain range by adjusting the pH value of the non-ironing finishing agent with the buffer, which is more conducive to the cross-linking reaction. The pH value buffer range of disodium hydrogen phosphate-citric acid buffer is 2.2-4.8, the pH value buffer range of citric acid-sodium citrate buffer is 3.0-4.8, and the pH value buffer range of acetic acid-sodium acetate buffer is 2.6-4.6.
[0063] In the present application, the adsorbent (nano adsorbent powder) generally has the following characteristics: large specific surface area, suitable pore structure and surface structure; strong adsorption capacity for adsorbate; generally no chemical reaction with adsorbate and medium; easy to manufacture and regenerate; excellent adsorption and mechanical properties. Adsorbents can be classified according to pore size, particle shape, chemical composition, surface polarity, etc., such as coarse pore and fine pore adsorbents, powder, granular, etc. Nano adsorbent powders include silica gel (preferably inorganic silica gel, more preferably silica gel desiccant), activated alumina, molecular sieve (zeolite molecular sieve), etc. Silica gel is preferably inorganic silica gel. Silica gel has an open porous structure and a large specific surface area (surface area per unit mass). It can adsorb many substances and is a very good desiccant and adsorbent. Activated alumina is a porous, highly dispersed solid material with a large surface area and a large number of micropores. The activated alumina has uniform particle size, smooth surface, high mechanical strength, strong hygroscopicity, and does not swell or crack after absorbing water, and remains in its original state. It is non-toxic, odorless, and insoluble in water and ethanol. Activated alumina is an efficient desiccant for deep drying of trace water. Molecular sieve is a synthetic desiccant with strong adsorption for water molecules. It is a crystalline aluminum silicate compound with regular and uniform pores in its crystal structure. The pore size is of the order of magnitude of the molecular size. Under ultra-low humidity conditions, it can still absorb a large amount of water in the environment, effectively controlling the environmental humidity. It absorbs moisture very quickly and absorbs a large amount of water in a very short time.
[0064] In the present application, nanofiber refers to ultrafine fiber with a fiber diameter less than 1000 nanometers. There are many methods for manufacturing nanofibers, such as stretching, template synthesis, self-assembly, microphase separation, electrospinning, etc. Among them, electrospinning is widely used due to its simple operation, wide application range, and relatively high production efficiency. The preferred nanofiber is carbon nanotube.
[0065] In the present application, the cellulose is preferably at least one of polymerized cellulose, lignin fiber, cellulose ether, methyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose and carboxymethyl cellulose.
[0066] In the present application, whiskers are short fibers of micro-nano scale grown from high-purity single crystals. Whiskers can be divided into two categories: organic whiskers and inorganic whiskers. Organic whiskers mainly include cellulose whiskers, poly(butyl acrylate-styrene) whiskers, poly(4-hydroxybenzyl ester) whiskers (PHB whiskers), etc.; inorganic whiskers mainly include ceramic whiskers (SiC, potassium titanate, aluminum borate, etc.), inorganic salt whiskers (calcium sulfate, calcium carbonate, etc.) and metal oxide whiskers (aluminum oxide, zinc oxide, etc.).
[0067] The methods and devices not described in detail in the present invention are all prior art and will not be described in detail.
[0068] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.
[0069] Example 1
[0070] A method for processing a moisture-absorbing quick-drying ready-made non-ironing shirt according to Example 1 comprises the following steps performed in sequence:
[0071] 1) spraying the non-ironing finishing agent by atomization, evenly applying the non-ironing finishing agent to the shirt, and controlling the liquid carrying rate of the shirt to be 50wt%;
[0072] Wherein, the non-ironing resin is selected from modified dihydroxymethyl dihydroxyethylene urea;
[0073] The fiber protective agent is a silicone emulsion of elastic polyurethane;
[0074] The catalyst is magnesium chloride;
[0075] The softener is selected from amino polysiloxane containing polyether groups;
[0076] The pH regulator is acetic acid;
[0077] 2) Pre-drying: pre-drying the shirt obtained in step 1) until the shirt is 50% dry;
[0078] 3) Pressing: Pressing each part of the shirt obtained in step 2) respectively, the pressing process conditions are pressure 2-5Kg, temperature 90℃~170℃, time 15-35s, pressing each part of the shirt, the pressing time, temperature and pressure are determined according to the fabric and the part of the shirt;
[0079] 4) Baking: Baking the pressed shirt obtained in step 3) at 100° C. for 5 minutes;
[0080] 5) Freezing: The baked shirt obtained in step 4) is placed in a freezer for freezing. The freezing process conditions are a freezing temperature of 0° C. and a freezing treatment time of 0.1 h.
[0081] 6) washing and drying to obtain a moisture-absorbing, quick-drying, iron-free shirt;
[0082] The content of components in the non-ironing finishing agent is: non-ironing resin 130g / L, fiber protective agent 30g / L, softener 40g / L, catalyst 20g / L, nano adsorbent powder 40g / L;
[0083] The nano-adsorbent powder comprises at least one of silica gel, activated alumina and molecular sieve, and the particle size of the nano-adsorbent powder is 10nm-200nm;
[0084] The pH value of the permanent iron finishing agent is 4.75;
[0085] A manual pre-ironing process is also provided between step 2) and step 3). The manual pre-ironing process is to manually iron the parts of the shirt obtained in step 2) so that creases are formed, and step 3) is to press along the creases. Manual pre-ironing generally uses pre-ironing tools corresponding to the parts of the shirt so that creases are formed on the shirt. However, the pressure and temperature of pre-ironing are far different from those of pressing, and the shaping effect of pressing cannot be achieved.
[0086] Example 2
[0087] The remaining technical solutions of Example 2 are the same as those of Example 1 except for the following:
[0088] 1) Control the shirt liquid content to 90wt%;
[0089] 2) Tumble dry the shirt until 90% dry;
[0090] 3) The process conditions of pressing are pressure 5Kg, temperature 170℃, and time 25s;
[0091] 4) The baking process conditions are 125°C and the baking time is 15 minutes;
[0092] 5) The freezing process conditions are a freezing temperature of 5°C and a freezing treatment time of 2h;
[0093] The content of components in the non-ironing finishing agent is: non-ironing resin 200g / L, fiber protective agent 10g / L, softener 60g / L, catalyst 15g / L, nano adsorbent powder 50g / L, fibrous connecting material 25g / L;
[0094] The nano-adsorbent powder comprises at least one of silica gel, activated alumina and molecular sieve, and the particle size of the nano-adsorbent powder is 10nm-200nm;
[0095] The fibrous connecting material comprises at least one of nanofibers, cellulose and whiskers, and the outer diameter of the fibrous connecting material is 10nm-200nm;
[0096] The pH value of the permanent iron finishing agent is 3.5;
[0097] The non-ironing resin is modified alkyl dihydroxyethylene urea;
[0098] The fiber protective agent is a mixture of a silicone emulsion selected from elastic polyurethane and a co-emulsification product of oxidized polyethylene homopolymer and amino silicone oil, with a mixing mass ratio of 1:1;
[0099] The catalyst is composed of a metal salt catalyst and a hydroxycarboxylic acid, the metal salt catalyst is zinc nitrate, the hydroxycarboxylic acid is 2,3-dihydroxysuccinic acid, and the mass percentage of zinc nitrate in the composite catalyst is 90%;
[0100] The pH adjuster was sodium dihydrogen phosphate-citric acid buffer.
[0101] Example 3
[0102] The remaining technical solutions of Example 3 are the same as those of Example 1 except for the following:
[0103] 1) Control the shirt liquid content to 70wt%;
[0104] 2) Tumble dry the shirt until 70% dry;
[0105] 3) The process conditions of pressing are pressure 3.5Kg, temperature 130°C, and time 35s;
[0106] 4) The baking process conditions are 150°C and the baking time is 25 minutes;
[0107] 5) The freezing process conditions are a freezing temperature of 10°C and a freezing treatment time of 10 h;
[0108] The content of components in the non-ironing finishing agent is: non-ironing resin 60g / L, fiber protective agent 50g / L, softener 20g / L, catalyst 125g / L, nano adsorbent powder 45g / L, fibrous connecting material 20g / L;
[0109] The nano-adsorbent powder comprises at least one of silica gel, activated alumina and molecular sieve, and the particle size of the nano-adsorbent powder is 10nm-200nm;
[0110] The fibrous connecting material comprises at least one of nanofibers, cellulose and whiskers, and the outer diameter of the fibrous connecting material is 10nm-200nm;
[0111] The pH value of the permanent iron finishing agent is 6;
[0112] The non-ironing resin is a mixture of modified dihydroxymethyl dihydroxyethylene urea and nano-dispersed self-crosslinking polyether polyurethane, with a mixing mass ratio of 2:1;
[0113] The fiber protective agent is a mixture of a co-emulsification product of oxidized polyethylene homopolymer and amino silicone oil;
[0114] The catalyst is composed of a metal salt catalyst and a hydroxycarboxylic acid, wherein the metal salt catalyst is zinc chloride, the hydroxycarboxylic acid is dimethylolpropionic acid, and the mass percentage of magnesium nitrate in the composite catalyst is 85%;
[0115] The pH adjuster was citric acid-sodium citrate buffer.
[0116] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for processing a moisture-absorbing quick-drying ready-made non-ironing shirt, characterized in that: The method includes the following steps in sequence: 1) uniformly spraying a non-ironing finishing agent on the outer surface and the inner surface of the shirt, wherein the non-ironing finishing agent contains a nano adsorbent powder, and the nano adsorbent powder includes at least one of silica gel, activated alumina and molecular sieve; 2) Pre-baking: pre-baking the shirt obtained in step 1); 3) Pressing: Pressing each part of the shirt obtained in step 2) respectively; 4) Baking: Baking the pressed shirt obtained in step 3); 5) Freezing: The baked shirt obtained in step 4) is placed in a freezer for freezing; 6) washing and drying to obtain a moisture-absorbing, quick-drying, iron-free shirt; Wherein, the temperature of the freezing chamber in step 5) is 0-10°C, and the freezing treatment time is 0.1h-10h.
2. The method for processing a moisture-absorbing quick-drying ready-made non-ironing shirt according to claim 1, characterized in that: The non-ironing finishing agent contains: 60-200 g / L of non-ironing resin, 10-50 g / L of fiber protective agent, 20-60 g / L of softener, and 15-25 g / L of catalyst; The pH value of the easy-ironing finishing agent is 3.5-6.
3. A method for processing a moisture-absorbing quick-drying ready-made non-ironing shirt according to claim 1 or 2, characterized in that: The content of the nano-adsorbent powder in the permanent-ironing finishing agent is 30-70 g / L, and the particle size of the nano-adsorbent powder is 10 nm-10000 nm.
4. A method for processing a moisture-absorbing quick-drying ready-made non-ironing shirt according to claim 1 or 2, characterized in that: The non-ironing finishing agent further comprises a fibrous connecting material, wherein the fibrous connecting material comprises at least one of nanofibers, cellulose and whiskers; The content of the fibrous connecting material in the non-ironing finishing agent is 20-60 g / L, and the particle size of the fibrous connecting material is 10 nm-10000 nm.
5. The method for processing a moisture-absorbing quick-drying ready-made non-ironing shirt according to claim 1, characterized in that: A manual pre-ironing process is also arranged between step 2) and step 3). In the pre-ironing process, each part of the shirt obtained in step 2) is provided with creases by manual ironing, and step 3) is performed by pressing along the creases.
6. The method for processing a moisture-absorbing quick-drying ready-made non-ironing shirt according to claim 1, characterized in that: Step 1) the shirt has a liquid content of 50% to 90% after applying the non-ironing finishing agent; After the pre-drying in step 2), the shirt is dehydrated by 50% to 90%.
7. The method for processing a moisture-absorbing quick-drying ready-made non-ironing shirt according to claim 1, characterized in that: The baking temperature in step 4) is 100° C. to 150° C., and the baking time is 5 min to 25 min.